1989
DOI: 10.1073/pnas.86.23.9485
|View full text |Cite
|
Sign up to set email alerts
|

Sequential effects of interleukin 2-diphtheria toxin fusion protein on T-cell activation.

Abstract: The interleukin 2-diphtheria toxin-related fusion protein (IL-2-toxin) rapidly inhibits protein synthesis in IL-2 receptor (IL-2R)-bearing phytohemagglutinin-activated T cells but transiently stimulates DNA synthesis. At 7 hr after interaction with IL-2R+ phytohemagglutinin-activated T cells, IL-2-toxin-treated cells bear augmented steady-state levels of c-myc, interferon y, and IL-2R mRNA; these effects are indistinguishable from those produced by recombinant IL-2. Amplification of IL-2 sequences by the polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 23 publications
0
22
0
Order By: Relevance
“…These findings accord with those of previous studies by Wild et al (32), who showed that conjugates of VEGF and DT were highly toxic to log-phase cells but were not toxic to confluent endothelial cells. The greater sensitivity of dividing endothelial cells to VEGF-toxin constructs may be because of differences in intracellular routing or catabolism of the construct as observed with other targeted therapeutic agents (49).…”
Section: Discussionmentioning
confidence: 99%
“…These findings accord with those of previous studies by Wild et al (32), who showed that conjugates of VEGF and DT were highly toxic to log-phase cells but were not toxic to confluent endothelial cells. The greater sensitivity of dividing endothelial cells to VEGF-toxin constructs may be because of differences in intracellular routing or catabolism of the construct as observed with other targeted therapeutic agents (49).…”
Section: Discussionmentioning
confidence: 99%
“…Denileukin diftitox has been shown to initiate signal transduction with ligand engagement, even if receptor-mediated internalization of the fusion toxin does not occur. 12 Signaling events mediated by rexinoids and IL-2R-ligand engagement may contribute to the markedly enhanced cytotoxicity observed in this study.…”
Section: Discussionmentioning
confidence: 85%
“…As shown, low doses of denileukin diftitox alone were associated with increased proliferation, presumably due to cytokinemediated signaling events from binding of denileukin diftitox to intermediate-and low-affinity receptor-expressing cells. 12 To confirm that inhibition of protein synthesis corresponded to increased cytotoxicity, MTT assays were performed. Bexarotene had a greater effect on enhancing cytotoxicity of denileukin diftitox than alitretinoin in both T-and B-leukemia cells, concordant to the degree of protein synthesis inhibition (Figure 4).…”
Section: Effects Of Rexinoids On T-and B-leukemia Cellsmentioning
confidence: 99%
“…Treatment of activated T-cells with a recombinant IL-2-diphtheria-toxin fusion molecule leads to initial stimulation of DNA synthesis and gene transcription through the activity of the IL-2 domain (Walz et al, 1989). Similarly, growth-factortoxin fusion molecules such as TGF-a-PE40 at low doses or (Fan etal., 1993).…”
Section: Discussionmentioning
confidence: 97%